Monitoring of Forest and Land Fires by the Regional Disaster Management Agency of South Kalimantan Province through the LAPAN Application: Fire Hotspot - Muhammad Shaufi Taqiyuddin; Ahmad Robiansyah Awaly; Muhammad Dheva Aditama; Annisa Zahra; Marshela Manurung; Mujahidin (IHSA Institute, 2022)
As a country that has a very high potential related to forest and land fires (karhutla), Indonesia especially South Kalimantan Province needs to have media that can be used in efforts to manage disasters such as forest and land fires more effectively. The benefit of this study is to find out the efforts of the South Kalimantan Disaster Management Agency (BPBD) in tackling the karhutla disaster that occurred. The method used is a descriptive qualitative study which is carried out through the study of literature related to the topic of discussion, journals, articles, books, to research results. The result of our study to show up how the utility of LAPAN : Fire Hotspot as one of the ICT-based media in dealing with disasters such as forest and land fires has various benefits and great advantages. This media can provide an overview related to disasters, especially forest and land fires such as statistical data, risk indexes, and spatial planning. From this study, we can be conclude this LAPAN : Fire Hotspot will have great benefits if it is used properly by the community, government, and other interested parties. Therefore, it is necessary to provide sufficient literacy and information regarding the use of this application, especially to the South Kalimantan BPBD as the front guard in tackling the problem of forest fires in South Kalimantan.